Factors associated with depression in the Nursing field: bibliographic review (Research, Society and Development, 2020)
The act of caring for others developed by nursing professionals is what defines this profession. However, it has been observed that different factors have influenced the quality of the services provided, such as the exhaustive workload, high stress in the work environment, double hours and Burnoult syndrome that characterize situations that have led nurses to develop depression. The objective of this study is to verify the increase in cases of depression among nurses, seeking to understand what factors are contributing to these indexes. Through bibliographic review it was possible to find different studies that deal with depression within nursing as well as ways of presenting, worsening, ways to avoid them or mitigate the growing cases. The major concern is in the growing rates of suicide among these professionals. It is necessary that there is special attention, with looks focused on the care, monitoring, treatment and recovery of nurses aiming at their well-being, quality of life and health. Only being physically and psychologically well will the nurse be able to develop their work effectively.